To find the solution set of the compound inequality \(2x + 1 = -5\) or \(x - 1 > -4\), we will solve each part separately.
-
Solving \(2x + 1 = -5\):
\[ 2x + 1 = -5 \] Subtract 1 from both sides: \[ 2x = -6 \] Divide both sides by 2: \[ x = -3 \]
-
Solving \(x - 1 > -4\):
\[ x - 1 > -4 \] Add 1 to both sides: \[ x > -3 \]
Now, we combine the results:
- From \(2x + 1 = -5\), we found \(x = -3\).
- From \(x - 1 > -4\), we found \(x > -3\).
Since the compound statement is connected by "or", the solution set includes any \(x\) that satisfies either part of the equation. Therefore, the solution set can be expressed as:
\[ x \geq -3 \quad \text{(since } x = -3 \text{ also satisfies the inequality } x > -3\text{)} \]
Thus, the solution set is:
\[ { x \mid x \geq -3 } \]
So the correct response is:
\({ x \mid x \geq -3 }\).